ANALISIS PENYEBAB KERUSAKAN WIRE ROPE CRANE PADA SAAT BONGKAR MUAT DI MV. AURORA CHRISTINE - Alif Fadhil; Endang Lestari; Nur Alamsyah (STKIP Subang, 2026)
This study aims to analyze the factors causing damage to the crane wire rope during loading and unloading operations on MV. Aurora Christine and to formulate corrective measures. The research method used is descriptive qualitative with a case study approach. Data were obtained through direct observation, semi-structured interviews, and documentation during sea practice. The analysis method used is the Miles and Huberman interactive model. The results indicate that wire rope crane damage was caused by three main factors: human factors (weak supervision by officers, lack of crew competence, and inconsistent inspection implementation), technical factors (limited spare parts, damaged sheaves and drums, and unscheduled lubrication), and procedural factors (reactive maintenance, suboptimal logbook recording, and low compliance with the Planned Maintenance System/PMS). The impacts of these obstacles include loading and unloading process delays, increased operational costs, disrupted voyage schedules, and increased occupational safety risks. The efforts undertaken to overcome these obstacles include enhanced officer supervision, implementation of routine inspection and lubrication, crew technical training, maintenance of supporting components, and application of wire rope replacement procedures according to ISO 4309:2017 and IMO Guidelines. Consistent implementation of Standard Operational Procedures (SOP) is expected to prevent recurring damage and maintain compliance with SOLAS and ISM Code regulations.